Frequency distribution of cytokine and associated transcription factor single nucleotide polymorphisms in Zimbabweans: Impact on schistosome infection and cytokine levels. - Andrew John Hanton; Fiona Scott; Katharina Stenzel; Norman Nausch; Grace Zdesenko; Takafira Mduluza; Francisca Mutapi (Public Library of Science (PLoS), 2022)
Cytokines mediate T-helper (TH) responses that are crucial for determining the course of infection and disease. The expression of cytokines is regulated by transcription factors (TFs). Here we present the frequencies of single nucleotide polymorphisms (SNPs) in cytokine and TF genes in a Zimbabwean population, and further relate SNPs to susceptibility to schistosomiasis and cytokine levels. Individuals (N = 850) were genotyped for SNPs across the cytokines IL4, IL10, IL13, IL33, and IFNG, and their TFs STAT4, STAT5A/B, STAT6, GATA3, FOXP3, and TBX21 to determine allele frequencies. Circulatory levels of systemic and parasite-specific IL-4, IL-5, IL-10, IL-13, and IFNγ were quantified via enzyme-linked immunosorbent assay. Schistosoma haematobium infection was determined by enumerating parasite eggs excreted in urine by microscopy. SNP allele frequencies were related to infection status by case-control analysis and logistic regression, and egg burdens and systemic and parasite-specific cytokine levels by analysis of variance and linear regression. Novel findings were i) IL4 rs2070874*T's association with protection from schistosomiasis, as carriage of ≥1 allele gave an odds ratio of infection of 0.597 (95% CIs, 0.421-0.848, p = 0.0021) and IFNG rs2069727*G's association with susceptibility to schistosomiasis as carriage of ≥1 allele gave an odds ratio of infection of 1.692 (1.229-2.33, p = 0.0013). Neither IL4 rs2070874*T nor IFNG rs2069727*G were significantly associated with cytokine levels. This study found TH2-upregulating SNPs were more frequent among the Zimbabwean sample compared to African and European populations, highlighting the value of immunogenetic studies of African populations in the context of infectious diseases and other conditions, including allergic and atopic disease. In addition, the identification of novel infection-associated alleles in both TH1- and TH2-associated genes highlights the role of both in regulating and controlling responses to Schistosoma.